Hydrocarbon Degradation Competence of Bacterial Consortium Isolated from Oil Polluted Soil in Azuabie Town, Port Harcourt, Nigeria (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Spills from artisanal hydrocarbon processing in Port Harcourt, Nigeria's Niger Delta, have devastated the local flora and fauna. Microbial consortiums can modify metabolic pathways and reduce hydrocarbon pollution. This study investigated the degradation efficiency of a bacterial consortium composed of Escherichia coli., Klebsiella sp., Lactobacillus sp., Enterobacter sp., Proteus sp., and Serratia sp., isolated from recurrently polluted soil in Azuabie Town Trans Amadi, Port Harcourt, with total petroleum hydrocarbon (TPH) concentration of 1487.24181 mg/kg and polycyclic aromatic hydrocarbons (PAHs) concentration of 12.852 mg/kg, a value higher than the Nigerian Midstream and Downstream Petroleum Regulatory Authority (NPRA), intervention limit of 5000 mg/kg and 40 mg/kg. Soil samples were aseptically collected with a sterile spatula at 15 cm depth. Microbial isolation was done using enrichment and enumerated via the vapour phase transfer techniques in the Bushnell Haas medium. A colorimetric assay using a 2,6-dichlorophenol indophenol (DCPIP) redox indicator was employed to determine the biodegradation potentials of the isolates. Total diesel degrading bacteria ranged at 2.2 × 106 cfu/g, kerosene degrading bacteria ranged at 3.2 × 106 cfu/g, premium motor spirit oil-degrading bacteria ranged at 4.4 × 106 cfu/g, and engine oil-degrading bacteria ranged at 2.0 × 106 cfu/g. Bacterial strain from the genera Escherichia coli., Klebsiella sp., Lactobacillus sp., Enterobacter sp., Proteus sp., and Serratia sp., utilized diesel, kerosene, premium moto spirit oil and engine oil as carbon sources. The polluted site's indigenous bacterial community can perform natural attenuation and breakdown hydrocarbons for in situ and ex situ bioremediation.
Keywords: Hydrocarbon degradation; Bacterial consortium; Oil-polluted soil; Port Harcourt; Niger Delta region